Synthesis and application of hierarchical mesoporous HZSM-for biodiesel production from shea butter - Alaba, P.A.; Sani, Y.M.; Mohammed, I.Y.; Abakr, Y.A.; Daud, Wan Mohd Ashri Wan (Elsevier, 2016)
Here, we report the upgrading of shea butter to biodiesel with hierarchical mesoporous ZSM-zeolites (HMZeol). Shea butter is a triglyceride (mainly oleic and steric acid) extracted from African shea tree nut. The catalysts synthesis was by desilication of conventional ZSM-with an aqueous solution of NaOH (0.3 and 0.4 M). XRF, XRD, NH3-TPD and N2 adsorption unveiled the effect of desilication of the parent zeolite. The study investigated the effect of NaOH concentration on matrix area, pore size, mesopore volume and Si/Al ratio. HMZeol showed superior activity on biodiesel yield when compared with the parent ZSM-zeolite. The catalytic material treated with 0.4 M NaOH (0.4HMZeol) gave 74% biodiesel yield at 5:1 methanol/oil molar ratio, 1 wt% catalyst, and 200°C for 3 h reaction time while ZSM-gave 46.05% yield under the same reaction conditions. Further increase in the reaction time to 12 h for 0.4HMZeol, 0.3HMZeol and ZSM-gave 82.12, 79.21, and 72.13% biodiesel yield respectively. These results showed that hierarchical mesoporous HZSM-is a promising solid acid catalyst for biodiesel production via methanolysis.